Analisis Inklusi Keuangan dan Pertumbuhan Inklusif terhadap Kesempatan Kerja dan Ketimpangan Pendapatan di Indonesia : Menggunakan Pendekatan Panel Simultan - Ningsih, Sri; Alfisyahri, Nuriah; Irawan, Deki; Putra, Rian (Universitas Muhammadiyah Surabaya, 2025)
This study aims to analyze the relationship between Financial Inclusion and Inclusive Growth in Indonesia. Financial inclusion is calculated using the Financial Inclusion Index, Inclusive Growth is measured using the Poverty Equivalent Growth Rate (PEGR) method. This study used the Simultaneous Panels data with the ILS (Indirect Least Square) method to analyze the effect of exogenous variables on endogenous variables. Utilizing secondary data, the data in this study is time series and cross-sections from 2019 – 2023. The results of this study conclude that financial inclusion in Indonesia is still